STRATEGI YAYASAN REYOG PONOROGO INDONESIA UNTUK KELANGSUNGAN KESENIAN REYOG PONOROGO PROVINSI JAWA TIMUR - Sigit Wahyu Riyadi; Joko Pramono; Aris Tri Haryanto (JI@P, 2023)
Reyog Ponorogo is a legacy of works of art from the ancestors of the Indonesiannation that has survived centuries until now is still able to survive because ReyogPonorogo has a very important function and role in people's lives in Ponorogo.The purpose of this research is to describe the strategies and obstacles of theReyog Ponorogo Foundation in the continuity of the Reyog Ponorogo arts.The results of the research show that the S-O Strategy, namely the Art of ReyogPonorogo, is the final form of a long development process that containsphilosophical, religious and educational values that need to be preserved. The ST(Strenghts-Threats) Strategies for Reyog Development that have been collectedare: 1) Building a system of "inheritance" and regeneration of Konco ReyogPonorogo, 2) Organizing Routine Exercises and Performances, 3) MaintainingStandards, 4) Emphasizing Stories in Playing Reyog, 5) Building community andgovernment support, 6) Integrating Reyog in Ponorogo Culture and TourismPromotion. WT (Weaknesses-Threats) Strategy An original regional art that issecond to none in other regions and is now known by the wider community to theinternational scene. The WT (Weaknesses-Threats) strategy, Reyog which is themain attraction of Ponorogo Regency is preserved by holding reyog performancesevery full moon, reyog festival every year which is summarized in the grebeg suroevent and Ponorogo anniversary.Keyword : Reyog Ponorogo Foundation, Art of Reyog Ponorogo.